Дискурсивний підхід в історичному дослідженні: проблеми й перспективи (на прикладі вивчення рефлексій канадського суспільства щодо Холодної війни) - Ткаченко, В. (Сiверянський лiтопис, 2019)
Стаття присвячена дискурсивному підходу в історичному дослідженні, перспективам його застосування в модерній науці, а також проблемам, з якими стикається
як дифузія цього підходу, так і його використання. Огляд та аналіз дискусії в гуманітаристиці стосовно питання дозволяє зробити висновок, що даний підхід розкриває
широкі перспективи та можливості історичних досліджень. The article is devoted to the discursive approach in historical research, the prospects for
its application in modern science, as well as the problems facing the spread of this approach
and its use. There is an analysis of the historiography of the problem that allows us to
characterize the state of its study, the main approaches to its solution. The review and analysis
of the humanitarian debate on this subject suggest that this approach has broad cognitive
capabilities in the context of historical research interests. The article also examines the use
of discourse analysis conducted on Canadian public reflections on issues related to the Cold
War; so the article shows how the analysis of discourse can be used in specific studies in the
field of history of external relations. The author concludes that the use of discourse analysis
provides a new vector for the study of international relations, showing how ideologies and
social constants and values of both society and political elites influence the formation of a
foreign policy course.